Administration of justice: Administrative tribunals and criminal justice system - Mathur, B.C. (1999)
Concerned with the problem of delays and backlog in courts, and falling values of jurisprudence, the author briefly discusses utilisation of other available channels. Picking up Administrative Tribunals, he discusses rationale of its creation, functioning and its down-grading following recent Supreme Court judgement. He then takes up our criminal justice system and discusses role of Bar and need for coordination and cooperation between Judiciary and Executive to maintain Rule of Law. - Reproduced
Keywords: Criminal law - India; Administrative tribunals - India; Administrative tribunals